Targeting hexokinase 2 to enhance anticancer efficacy of trichosanthin in HeLa and SCC25 cell models - Yan Zhou; Maoxin Ran; Wenying Shan; Kaifang Wang; Ou Sha; Kin Tam (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: Trichosanthin (TCS) is a plant-based ribosome-inactivating protein exhibiting a range of pharmacological properties, including abortifacient and anticancer. However, the routine clinical use in cancer treatment was hampered by its antigenicity. Hexokinase 2 (HK2) is a pivotal regulator of glycolysis, where aberrant expression is observed in many cancers. This study investigates the anticancer effects and mechanisms of TCS in combination with benserazide (Benz), a HK2 inhibitor, in Hela and SCC25 cancer models. Experimental approach: MTT, colony-formation and cell cycle assays were performed to assess the cytotoxic effects of TCS and Benz in HeLa and SCC25 cells. Seahorse assay, western blotting, flow cytometry analysis and RNA sequencing were employed to investigate the pharmacological effects of the combo treatment. SCC25 cell xenograft mouse model was established for in vivo efficacy study. Key results: Combined use of TCS and Benz exhibited synergistic anticancer effects in both Hela and SCC25 cell models. The observed synergistic effects were attributed to the modulation of glycolysis by targeting HK2, leading to reduced lactate production and increased ROS accumulation which further inhibited colony formation and cell cycle progression, as well as triggered apoptosis. Moreover, this combination effectively inhibited NFκB/ERK signalling pathways, which were found to be significantly activated upon single use of TCS. It was found that the combination significantly suppressed the tumour growth in SCC25 cell xenograft mouse model. Conclusion: Our findings suggested that targeting HK2 and modulating glycolysis may offer a promising avenue for improving the therapeutic outcomes of TCS-based anticancer treatments.